2022
DOI: 10.3389/fnetp.2022.833119
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Survival Modelling in Cirrhosis Using Parenclitic Networks

Abstract: Background: Liver cirrhosis involves multiple organ systems and has a high mortality. A network approach to complex diseases often reveals the collective system behaviours and intrinsic interactions between organ systems. However, mapping the functional connectivity for each individual patient has been challenging due to the lack of suitable analytical methods for assessment of physiological networks. In the present study we applied a parenclitic approach to assess the physiological network of each individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 58 publications
3
25
0
Order By: Relevance
“…Indeed, the results of this study corroborate previous research in the field, where changes in organ system connectivity measured using network analysis and other methods were shown to improve traditional scoring systems for predicting patient outcomes in patients with cirrhosis or even detecting subgroups of patients who may respond to therapy (e.g., targeted albumin therapy) [17,18,55,56]. Specifically, a previous study using parenclitic network analysis showed reduced organ system connectivity (based on population-level correlation network mapping) in patients with cirrhosis who did not survive compared with survivors [18].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Indeed, the results of this study corroborate previous research in the field, where changes in organ system connectivity measured using network analysis and other methods were shown to improve traditional scoring systems for predicting patient outcomes in patients with cirrhosis or even detecting subgroups of patients who may respond to therapy (e.g., targeted albumin therapy) [17,18,55,56]. Specifically, a previous study using parenclitic network analysis showed reduced organ system connectivity (based on population-level correlation network mapping) in patients with cirrhosis who did not survive compared with survivors [18].…”
Section: Discussionsupporting
confidence: 84%
“…We applied Parenclitic network mapping for network mapping based on patients’ clinical or biochemical biomarkers. Parenclitic network mapping is a novel approach for network analysis [17] that facilitates the mapping of individual data points within models constructed from a reference population (e.g., patients who survive ALF). Initially, the correlation between clinical/biochemical biomarkers was assessed in the reference population to determine the expected relationship between the pair of biomarkers.…”
Section: Methodsmentioning
confidence: 99%
“…Reduced complexity of cardiac time‐series as well as body temperature have already been reported in non‐survivors with sepsis (de Castilho et al, 2018; Papaioannou et al, 2012, 2013). Future studies can extend this type of computational analysis by including network analysis of parallel physiological variables for providing pathophysiologic insight as well as personalized physio‐markers for prognostication in critically ill patients (Moorman et al, 2016; Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…How to cite this article: Abid, N.-U., & Mani, A. R. (2022). The mechanistic and prognostic implications of heart rate variability analysis in patients with cirrhosis.…”
Section: Basic Requirements For Measurement Of Heart Rate Variability...mentioning
confidence: 99%
“…Due to the multisystem involvement in cirrhosis, a network physiology approach has been suggested for the optimum assessment of patients suffering from chronic liver failure (Tan et al, 2020 ; Zhang et al, 2022 ). Crucially, a network physiology approach may help develop physio‐markers to create novel prognostic indicators for patients with cirrhosis, which has been the subject of investigation by recent studies (Bhogal et al, 2019 ; Bottaro et al, 2020 ; Chan et al, 2017 ; Jansen et al, 2018 , 2019 ; Mani et al, 2009 ; Satti et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%